The city of Lisbon in the preparation for the conquest of Ceuta - Silva, Carlos Guardado da (2015)
D. João I had the idea, at least since 1409, of carrying out a large military enterprise that could serve to knight his sons. The preparations began in 1411, stepping up after the Royal Council of Torres Vedras, held in July 1414. Once the armada had been announced to depart in the 1415 celebrations of St. John’s, the king had to ensure its organisation, supplying the ships with artillery and weapons. The ships were equipped in Lisbon before heading to Ceuta. To Lisbon would also converge men, products and efforts from the entire kingdom, as well silver, copper and the necessary food for the men who prepared the armada, leading to a workload increase in the ‘taracenas’ (royal arsenal). Conquered the Islamic city, the Portuguese monarch was able to knight his sons, having the enterprise contributed not only to legitimize the kingdom and the first king of the new dynasty of Avis, a path that had started some years earlier in Aljubarrota (1385), but also to enhance the prestige and power of the Portuguese kingdom within Christianity and, above all, within the Iberian context.